Adsorptive removal of 2,4-dichlorophenoxyacetic acid from aqueous solution using bagasse fly ash as adsorbent in batch and packed-bed techniques - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Clean Technologies and Environmental Policy, 2016)
Among the several synthetic herbicides available currently, 2,4-D is a commonly used herbicide to control broadleaf weeds in agriculture and forestry. However, its increasing use in agricultural and nonagricultural activities has resulted in increasing concentrations of 2,4-D being detected in water bodies. Thus, there is a need to identify methods to remove 2,4-D to protect the environment. Among the various methods used for 2,4-D removal, adsorption is found to be effective, and several adsorbents have been studied to remove 2,4-D from aqueous solutions. In this study, we used bagasse fly ash (BFA), a common industrial waste generated in large amount worldwide, for 2,4-D removal from aqueous solution using batch and continuous packed-bed adsorption. In the batch adsorption process, the effects of initial concentration, contact time, temperature, pH, and particle size of BFA were studied. The packed-bed performance of BFA was investigated by varying the influent concentration (50-150 mg/L), flow rate (1.2-4 mL/min), and bed height (4.5-9 cm). Isotherm and thermodynamic parameters are determined for batch adsorption, whereas the performance of continuous adsorption is evaluated by different packed-bed models. The particle-size effect indicated the higher removal of 2,4-D on the bigger particles of BFA due to greater BET surface area and carbon-to-silica ratio than smaller particles. The maximum percentage removal (37.04) is achieved for an influent concentration of 50 mg/L, flow rate of 1.2 mL/min, and bed height of 6.5 cm. For the first time ever, the deactivation kinetic model was applied for the solid-liquid adsorption system and it showed the best fit among the selected models. The bed capacity (m(2)/g) of BFA is three times greater than synthetic activated carbon for adsorption of 2,4-D. This informs that the BFA can be used as an adsorbent for 2,4-D removal from aqueous solution.

Adsorptive removal of diuron on biomass ashes: a comparative study using rice husk ash and bagasse fly ash as adsorbents - Deokar, Sunil K.; Singh, Diksha; Modak, Sweta; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Desalination and Water Treatment, 2016)
This study describes the use of two types of biomass ashes (BMAs) as adsorbents for diuron removal. Two BMAs, namely rice husk ash (RHA) and bagasse fly ash (BFA), were used in this study, and their adsorption behavior and adsorption mechanism were compared based on various characteristics, such as surface area, pore diameter, and volume. It was found that the particle size and the composition of these BMAs, especially the content of carbon and silica, primarily affect the adsorption kinetics and capacity. Compared with RHA, BFA has more carbon content (47.37%), and therefore shows higher adsorption capacity (43.48mol/g). In addition, BFA has larger external surface area and exhibited faster kinetics at the initial adsorption stage; by contrast, RHA due to its larger pore diameter allows for faster pore adsorption and surpasses the initial kinetic rate of BFA. For the same particle size (0.354-0.251mm), the equilibrium capacity of BFA was found to be four times greater than that of RHA; in addition, the surface area of BFA is two times more than that of RHA, suggesting that BFA has more active sites than RHA. It was found that solution pH influences adsorption mechanism of diuron molecule on BMA. The uptake capacity of BFA and RHA is 10 times greater than natural adsorbents such as soil and is comparable with synthetic adsorbents such as activated carbon and multiwalled carbon nanotubes. To our knowledge, removal of diuron using ashes has not been reported previously.

Agro-industrial waste: a low cost adsorbent for effective removal of 4-chloro-2-methylphenoxyacetic acid herbicide in batch and packed bed modes - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
The present work describes the aqueous phase removal of 4-chloro-2-methylphenoxyacetic acid herbicide by rice husk ash (RHA) using batch and packed bed adsorption techniques. The effects of dosage, initial concentration, time, pH, temperature, and particle size of adsorbent in batch compared with effects of influent concentration, flow rate, and bed height in packed bed were studied. The particle size effect reveals that the removal is dependent on chemical composition (silica and carbon content) together with BET surface area of RHA. The aptness of Langmuir isotherm to batch data indicates the favorable adsorption whereas that of Temkin isotherm informs the heterogeneous nature of RHA. The kinetics of adsorption follows the pseudo-second order and Elovich models while thermodynamics of process indicates the exothermic adsorption. Among the models applied in packed bed study, the deactivation kinetic, Yoon-Nelson and bed depth service time (BDST) models are suitable to explain the packed bed adsorption. The adsorption capacity of RHA in packed bed study is found greater than that in batch. The adsorption capacity of RHA determined by the BDST model is 3019 mg/L for 90 % saturation of bed. The adsorption capacity of RHA based on weight is similar to 2.3 times and that based on surface area is similar to 55.55 times greater than that of granular activated carbon.

Behaviour of biomass multicomponent ashes as adsorbents - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2016)
Physico-chemical characteristics of rice husk ash and baggase fly ash, commonly referred to as biomass ashes enable their use as adsorbents. Contrary to normal expectations, it is observed that larger particles have more number, narrower and deeper pores than smaller particles. As a consequence they have higher pore volume, total surface area and hence adsorption capacity. Also, the uptake rate of adsorption depends on the silica to carbon ratio, which is seen to be smaller for larger particles and hence they take a longer time to reach equilibrium. The extent of carbon content determines the capacity, whereas silica to carbon ratio determines the kinetics of adsorption. Removal of 2,4-dichlorophenoxyacetic acid, from aqueous solution was chosen as a representative case for study and the results obtained are compared with earlier reported results.
Keywords: Adsorption capacity; bagasse; biomass ash; rice husk; silica to carbon ratio

Comparative evaluation of packed-bed performance of biomass ashes as adsorbents for removal of diuron from aqueous solution - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Desalination and Water Treatment, 2016)
The packed-bed performance of biomass ashes (BMA), namely rice husk ash (RHA) and bagasse fly ash (BFA), was investigated for adsorptive removal of diuron (herbicide) under dynamic conditions. The effects of influent concentration (10-30mg/L), flow rate (1-3mL/min), and bed height (3-11cm) were studied at 30 degrees C and results were analyzed using various packed-bed models. The saturation time and capacity of the BFA bed were found to be approximately 1.5 and 1.6 times higher due to higher BET surface area than that of RHA bed. However, the bed utilization of RHA was higher because of smaller mass transfer zone. At a constant influent concentration (20mg/L) and flow rate (1mL/min), the maximum volume of diuron treated was 1,325 and 1,685mL using RHA (bed height 10cm) and BFA (bed height 11cm), respectively. Among the packed-bed models applied, the BDST model revealed the inconsistent MTZ and complex mechanism involving more than one rate-controlling step for the adsorption of diuron on both ashes. The kinetics in the initial part of the breakthrough curve was governed by external mass transfer according to the Bohart-Adams and Wolborska models. Better agreements between experimental and predicted values of bed capacities for each ash and the higher bed capacity of BFA than RHA were demonstrated by the Thomas model. The Yoon-Nelson model was found to be superior for BFA rather than for RHA to estimate 50% saturation time. However, the deactivation kinetic model, previously discovered and applied only for gas-solid adsorption, was found to be the best for the diuron-BMA (liquid-solid) adsorption system in this study.